Permintaan Pangan Hewani Di Pedesaan Jawa Timur, Indonesia - Khoiriyah, Nikmatul; Anindita, Ratya; Hanani, Nuhfil; Muhaimin, Abdul Wahib (Universitas Islam Malang, 2018)
Households in rural East Java consume protein below the national protein adequacy standard. This study explains the effect of price, income and demographic variables on animal food demand using the Quadratic Almost Ideal Demand System model approach. The research data use the 2016 Susenas data. The results show that the increase in income increases the consumption of animal food. All animal food is a luxury item except eggs and preserved fish. Powdered milk is most sensitive to changes in income, followed by beef. Price increases reduce animal food consumption Income policies are more effective than price policies